The Influence of VTS and Mastercable Services on PNBP in the Class I Tanjungpinang Navigation District - Oktriyanto, Rakeen; Yanto, Meidi; Hasnarika; Meifari, Vanisa; Febrianta Chandra, Rezario (Summa : Journal of Accounting and Tax, 2025)
This research aims to analyze the influence of Vessel Traffic Service (VTS) and Mastercable services on Non-Tax State Revenue (PNBP) at the Tanjungpinang Type A Class I Navigation District Office. The study uses a quantitative approach by analyzing PNBP recapitulation data from 2020 to 2022. Data analysis techniques include classical assumption testing, multiple linear regression, and hypothesis testing, all conducted using Eviews version 12. The classical assumption tests confirm that the data meet the criteria of normality, and show no signs of multicollinearity, heteroscedasticity, or autocorrelation. The regression analysis demonstrates that both VTS and Mastercable variables have a significant and positive effect on PNBP. The results of the t-test support this conclusion, indicating that improvements in VTS and Mastercable services are associated with an increase in non-tax revenue. Furthermore, the coefficient of determination (R²) reveals that the VTS and Mastercable variables account for 70.45% of the variation in PNBP during the observed period. These findings highlight the strategic role of navigation services in optimizing state revenue outside of taxes, and support efforts to enhance service innovation and system integration to further improve performance and financial outcomes in the maritime sector.